Teaching How to Learn:: Reconsidering Architectural Design in Undergraduate Education - HESHMATI, Ali; SINGH, Virajita (ARCC Conference Repository, 2019)
This paper examines an architectural design studio, which puts a strong emphasis on the role of research in design process. The co-authors taught collaborative parallel architectural design studios consecutively in spring, fall semesters of 2001, and spring semester of 2002. An ongoing research tests the effectiveness of efforts made by the authors to re-examine the priorities for the undergraduate curriculum through the second level studio in architectural design offered to students of the Bachelor of Arts (BA) and Bachelor of Science (BS) degree programs. The efforts to refine and redefine priorities within the studio education were based on the following eight premises: 1. The main role of the studio teacher is to teach students how to learn. 2. Research is a crucial tool for design. 3. Learning about the environment and sustainability, in an elemental and direct way, is critical to design education. 4. Design is integrally related to and influenced by materials and methods out of which emerges a particular aesthetic. 5. Exposure to a diversity of ideas and viewpoints through guest speakers, reading assignments and other resources is invaluable to student development. 6. Creating opportunities for students to teach their peers and teachers accelerates their rate of development. 7. Learning through collaboration is a means of constructively harnessing student’s energy and conveys an often-neglected reality of the architectural profession. 8. Building, documentation, and exhibition of student’s work, both process and product, have the potential to positively engage the larger community The methods employed to test the effectiveness of the teaching efforts are observation, documentation, and analysis of student presentations and projects by the authors. Informal interviews of students and of guest speakers invited to the course also contributed to the research. The main results will be illustrated through specific student projects and more generally in the paper. Research is ongoing through the current semester.